2002
DOI: 10.3989/mc.2002.v52.i265.343
|View full text |Cite
|
Sign up to set email alerts
|

Determinación del contenido de OH<sup>-</sup> en la fase acuosa de los poros de matrices cementantes por un método empírico de lixiviación

Abstract: RESUMENEl método más fiable de determinación de iones hidroxilo en una fase acuosa de materiales cementantes es la extracción de la misma mediante aplicación de presión (pore-pressing). Sin embargo, este método necesita un equipo especial además de una cantidad de muestra relativamente alta. En la presente investigación, se propone la determinación de la concentración de OH' en la fase acuosa del hormigón mediante un método de lixiviación en muestra granulada. El programa experimental se ha realizado a partir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The second step of ESL methods generally involves stirring the powdered sample in a solvent, which is most commonly deionized water, and then filtering to obtain a diluted solution for chemical analysis. Several studies on ESL test methods have investigated in numerous factors, including the temperature of the leaching solution [10,16] (Natkunarajah et al recently showed a negligible effect of solution temperature on the results of ESL for concrete [24]), liquid-to-solid ratio [16][17][18][19][20], the duration of the leaching period [19,21,22], and the particle size of the pulverized sample [16,19,21,22]. The list of ex-situ leaching methods resulting from multiple studies includes cold water extraction (CWE) [9,18,19,[21][22][23][24], hot water extraction (HWE) [13,25], and the "espresso" method [11,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second step of ESL methods generally involves stirring the powdered sample in a solvent, which is most commonly deionized water, and then filtering to obtain a diluted solution for chemical analysis. Several studies on ESL test methods have investigated in numerous factors, including the temperature of the leaching solution [10,16] (Natkunarajah et al recently showed a negligible effect of solution temperature on the results of ESL for concrete [24]), liquid-to-solid ratio [16][17][18][19][20], the duration of the leaching period [19,21,22], and the particle size of the pulverized sample [16,19,21,22]. The list of ex-situ leaching methods resulting from multiple studies includes cold water extraction (CWE) [9,18,19,[21][22][23][24], hot water extraction (HWE) [13,25], and the "espresso" method [11,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on ESL test methods have investigated in numerous factors, including the temperature of the leaching solution [10,16] (Natkunarajah et al recently showed a negligible effect of solution temperature on the results of ESL for concrete [24]), liquid-to-solid ratio [16][17][18][19][20], the duration of the leaching period [19,21,22], and the particle size of the pulverized sample [16,19,21,22]. The list of ex-situ leaching methods resulting from multiple studies includes cold water extraction (CWE) [9,18,19,[21][22][23][24], hot water extraction (HWE) [13,25], and the "espresso" method [11,26]. These methods have been used to obtain the alkali metal content in g/g of dry sample -a useful metric for AAR studies [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation